2013
DOI: 10.1017/thg.2013.4
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Reserve and Anti-Mullerian Hormone (AMH) in Mothers of Dizygotic Twins

Abstract: This study aimed to explore if natural dizygotic (DZ) twinning is associated with earlier menopause and lower anti-Mullerian hormone (AMH) values. We investigated if advanced biological reproductive aging, which can be responsible for the multiple follicle growth in familial twinning, is similar to mechanisms that occur in normal ovarian aging, reflected by earlier menopause in mothers of DZ twins and lower levels of AMH. A total of 16 mothers of DZ twins enrolled with the Netherlands Twin Register (average ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Indeed, advanced ovarian aging is a recognized feature of familial DZ twinning, with reported lower levels of anti-Mullerian hormone (AMH), a marker of lower ovarian primordial follicular reserve. 57 The rs17293443-C allele in SMAD3 also increases chances of DZ twinning, but this effect appears independent of circulating FSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, advanced ovarian aging is a recognized feature of familial DZ twinning, with reported lower levels of anti-Mullerian hormone (AMH), a marker of lower ovarian primordial follicular reserve. 57 The rs17293443-C allele in SMAD3 also increases chances of DZ twinning, but this effect appears independent of circulating FSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Five to ten follicles are recruited from the oocyte pool per menstrual cycle in response to the rise in FSH secretion. Selection of a dominant follicle is thought to be regulated by AMH secreted by maturing follicle granulosa cells to suppress the growth of other follicles79,80. It is possible that the age-related rise in FSH and decline in AMH may disrupt mono-ovulation and increase the incidence of two oocytes being ovulated.…”
Section: Introductionmentioning
confidence: 99%
“…Van Asselt and colleagues argue that the capacity of remaining follicles to produce estrogens can be relevant as well for onset of menopause28. Another explanation might be the existence of counterbalancing protective mechanisms such as recruitment in wave-like fashion of less oocytes per cycles29 or longer cycle lengths so that the total number of ovulation in a lifetime is shortened30, supported by studies that showed an earlier age at menopause for mothers of dizygotic twins compared to control mothers31,32. Germline stem cells in adult human ovaries, which could be activated postnatally under specific circumstances33 could be another possibility but robust human data is necessary to support this hypothesis34,35.…”
Section: Discussionmentioning
confidence: 99%